Sistem Pemasaran Manggis di Bogor dan Tasikmalaya - Andriyanty, Reny; Aminda, Fadilla Ristya; Agustia, Devi; Sari, Ratna Mega (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The purpose of this study was to comprehensively examine the mangosteen marketing system in Bogor and Purwakarta.  The research methods used were qualitative and quantitative.  The results showed that the mangosteen marketing institutions in Bogor and Tasikmalaya Regencies consisted of farmers as producers, middlemen, collectors, exporters, and agro-industrial mangosteen processing institutions. In Bogor Regency, only 4 percent of farmers are ready to become marketing institutions capable of selling their products, while in Tasikmalaya Regency, the percentage is around 17 percent.  The farmer’s share of the price at the domestic consumer level indicates that the most effective marketing system is in Tasikmalaya, Purwakarta, and among mangosteen farmers in Bogor. The farmer’s share value for exported mangosteen in Bogor is 17.38, in Tasikmalaya it is 58.96, and in Purwakarta it is 48.78. The price formation process in both Bogor and Tasikmalaya districts is one-sided. Farmers tend to be price takers from the marketing institutions above them. An analysis of the correlation between the marketing institutions chosen by farmers and their income shows a fairly strong relationship of approximately 31.8 percent. Recommendations for improving the quality of mangosteen in Bogor, Tasikmalaya, and Purwakarta include the need for proper technical training in mangosteen cultivation and the production of organic products, accompanied by enhanced farmers' management capabilities regarding mangosteen marketing channels.